BRI Syariah Stock Price Assessment Analysis Before and After the Merger - Shinta Anggraeny; Iwan Suhasto; Dewi Kirowati (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
This study aims to determine the valuation of BRI Syariah stock prices before the merger and after the merger. The assessment of stock prices in this study uses fundamental analysis, which is an analysis used to determine the condition of the company by studying matters relating to the basic conditions or fundamentals of a company both quantitatively and qualitatively. Stock price assessments can use five ratios, namely the determination of stock prices in this study using five ratios, namely Earning Per Share (EPS), Price Earning Ratio (PER), Price to BooK Value (PBV), Debt To Equity Ratio (DER), Return On Equity (ROE). The object used in this research is Bank Rakyat Indonesia Syariah (BRIS), which is one of the state-owned Islamic banks which has been merged by the Ministry of SOEs. The results showed that the EPS value at the end of 2020 was 25.05, while in the first quarter of 2021 it fell to 18.08 and in the second quarter of 2021 it rose significantly to 36.00. The PER value at the end of 2020 was 89.80, while in the first quarter of 2021 it was 126.66 and in the second quarter of 2021 it fell significantly to 63.89. The PBV value tends to have a fairly stable change. At the end of 2020 it had a value of 4.09, while in the first quarter of 2021 it was 4.18 and in the second quarter of 2021 it was 4.05. The DER value also has a stable change and is still in a fairly high range of DER values. At the end of 2020 it has a value of 9.60, in the first quarter of 2021 it is worth 9.42 and in the second quarter it is 9.59. The ROE value at the end of 2020 had a value of 5.03, then in the first quarter of 2021 it rose to 14.42 and in the second quarter of 2021 it fell back to a value of 9.59.